Polyaniline-Doped Poly (Methyl Methacrylate) Microfiber for Methanol Sensing - Isa, Naimah Mat; Irawati, Ninik; Rahman, Husna Abdul; Yusoff, Mohd Hanapiah Mohd; Harun, Sulaiman Wadi (Institute of Electrical and Electronics Engineers (IEEE), 2018)
The main objective of this paper is to investigate the effect of Polyaniline (PANI) as a dopant in the fabrication of a polymer microfiber for sensing methanol. A simple direct drawing technique was employed in the preparation of a Poly (methyl methacrylate) (PMMA) doped with PANI microfiber. The changes of the power spectrum were measured through an optical spectrum analyzer over a range of 100-500 ppm methanol solution concentrations. It was observed that the sensor utilizing a PANI-doped microfiber had a higher response toward the changes in the methanol solution concentrations compared with its undoped counterpart with an improvement of 41.01% and more than 5 times for the sensitivity and resolution, respectively. A sensitivity of 0.047 dBm/ppm was attained with the use of a PMMA microfiber with a taper diameter and length of 3μm and 3 mm, respectively. The field emission scanning electron microscopy proved the successful doping of PANI into the PMMA microfiber, which contributed to the increase in the performance of the sensor.